(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Abstract. This article examines Leo Tolstoy’s story "Hadji Murad" in the context of writer’s creative research. As a result, it revealed that Tolstoy’s story on the one hand, exposes despotism and on other hand poeticizes rebelliousness and joyous personality. Based on the research, the author argues that the story goes against the teachings of Tolstoy’s non-violent resistance to evil underlying his Christian beliefs. Considered not only the history of the creation of the novel, but also the point of view of researchers about the novel’s issues and its genre. "Hadji Murad" is a shining example of how great realist Tolstoy was not afraid to speak out against Tolstoy preacher when required by the truth of life portrayed in the story. L.N. Tolstoy in the process of creating an image of the protagonist openly expressed admiration for the freedom-loving mountaineers and at the same time adheres to psychological set their inevitable occurrence in Russian civilized context.